Microsoft SQL server 2005 : applied techniques - Albert, Herbert (Step by step (Redmond, Wash.), 2006)
SQL Server 2005 is Microsoft's next-generation data management and analysis solution that delivers increased security, scalability, and availability to enterprise data and analytical applications while making them easier to create, deploy, and manage. This book shows readers with fundamental SQL Server skills, as well as new-to-topic but experienced database developers, techniques to design, build, test, deploy, and maintain better SQL Server databases. The format is a hands-on, sequential, developer's companion, providing beyond-the-basics guidance. This book is not a feature-driven reference manual, but a highly practical learning experience demonstrating how to build database solutions to solve business problems.